Contribution of AcrAB efflux pump to ciprofloxacin resistance in Klebsiella pneumoniae isolated from burn patients - Pakzad, Iraj; Zayyen Karin, Maasoume; Taherikalani, Morovat; Boustanshenas, Mina; Lari, Abdolaziz Rastegar (German Medical Science GMS Publishing House, 2013)
[english] Resistance to fluoroquinolones has been recently increased among bacterial strains isolated from outpatients. Multidrug-resistant is one of the major organisms isolated from burn patients and the AcrAB efflux pump is the principal pump contributing to the intrinsic resistance in against multiple antimicrobial agents including ciprofloxacin and other fluoroquinolones. Fifty-two isolated from burn patients in Shahid Motahari hospital and confirmed by conventional biochemical tests. Antimicrobial susceptibility testing was done according to CLSI 2011 guidelines, to determine the antimicrobial resistance pattern of isolates. A gene was detected among ciprofloxacin-resistant isolates by PCR assay. MICs to ciprofloxacin were measured with and without carbonyl cyanide . Forty out of the 52 isolated from burn patients in Shahid Motahari hospital were resistant to ciprofloxacin according to breakpoint of CLSI guideline. PCR assay for A gene demonstrated that all ciprofloxacin-resistant isolates harbored A gene coding the membrane fusion protein AcrA and is a part of AcrAB efflux system. Among these isolates, 19 strains (47.5%) showed 2 to 32 fold reduction in MICs after using CCCP as an efflux pump inhibitor. The other 21 strains (52.5%) showed no disparity in MICs before and after using CCCP. In conclusion, the AcrAB efflux system is one of the principal mechanisms contribute in ciprofloxacin resistance among isolates but there are some other mechanisms interfere with ciprofloxacin resistance such as mutation in target proteins of DNA gyrase of topoisomerase IV enzymes.